STRATEGY FOR OVERCOMING THE COMMUNITY'S NEGATIVE IMAGE TOWARD ISLAMIC BOARDING SCHOOLS - Umlina Mukhlas; Nur Rohim Yunus; Faiqatul Husna (Hijri, 2025)
Islamic boarding schools (pesantren), as traditional Islamic educational institutions in Indonesia, often face a negative public image portraying them as closed, rigid, and less adaptive to modern challenges such as radicalism, narcotics, and bullying. The background of this issue stems from stereotypes reinforced by mass and social media, which highlight cases of isolation without contextualizing positive aspects, as well as from the public's limited understanding of moderate Islamic values such as tolerance and empathy. This condition hinders the role of pesantren as agents of social change and as institutions shaping the character of the younger generation. This study employs both qualitative and quantitative methods, including surveys, in-depth interviews with pesantren leaders, alumni, and community members, as well as literature reviews to identify the factors contributing to stigma and strategies for its mitigation. This approach is grounded in philosophical, sociological, and juridical foundations, such as Law Number 18 of 2019 on Pesantren, which emphasizes adaptability and innovation. The findings indicate that effective strategies include curriculum modernization through the integration of general sciences and technology, social media campaigns to build positive narratives, anti-bullying programs through counseling and conflict resolution skills training, and partnerships with government and local communities for social initiatives such as narcotics prevention. The discussion reveals that these approaches successfully reduce stigma, strengthen public trust, and reinforce the inclusivity of pesantren as a safe and harmonious learning environment. The conclusion asserts that overcoming negative imagery requires multidimensional collaboration to realize the vision of pesantren as a relevant, inclusive, and competitive pillar of national education, thereby contributing to the development of a morally grounded generation in the modern era.